SIKAP PENGUNJUNG TAMAN EKSPRESI TERHADAP PELAYANAN INFORMASI FASILITAS KOTAK LITERASI CERDAS SEBAGAI SARANA BACA - Wanda Sri Maryati; Mariana Rista Ananda Siregar; Imani Satriani (Jurnal Penelitian Sosial Ilmu Komunikasi, 2021)
The study aims to analyze a visitor's attitude toward information services as a means of reading facilities. The model theory used in this study is the SMCR theory that stands for source, message, channel, and receiver. On this study researchers took the population in central bogor district as a population in bogor city, they were visitors or people who had already been to the expression park. The sample retrieval technique on this study uses purposive sampling. Researchers are using the slovin formula asa basis for sample from the population. The study employs two variables, X - characteristic variables of the visitor's age, gender, educational level, and work level while the Y attitude variables, cognitive, affective, and cumulative.